Environmental heterogeneity and biotic interactions mediate climate impacts on tropical forest regeneration. (22nd December 2017) - Uriarte, María; Muscarella, Robert; Zimmerman, Jess K.
Abstract: Predicting the fate of tropical forests under a changing climate requires understanding species responses to climatic variability and extremes. Seedlings may be particularly vulnerable to climatic stress given low stored resources and undeveloped roots; they also portend the potential effects of climate change on future forest composition. Here we use data for ca. 50, 000 tropical seedlings representing 25 woody species to assess (i) the effects of interannual variation in rainfall and solar radiation between 2007 and 2016 on seedling survival over 9 years in a subtropical forest; and (ii) how spatial heterogeneity in three environmental factors—soil moisture, understory light, and conspecific neighborhood density—modulate these responses. Community‐wide seedling survival was not sensitive to interannual rainfall variability but interspecific variation in these responses was large, overwhelming the average community response. In contrast, community‐wide responses to solar radiation were predominantly positive. Spatial heterogeneity in soil moisture and conspecific density were the predominant and most consistent drivers of seedling survival, with the majority of species exhibiting greater survival at low conspecific densities and positive or nonlinear responses to soil moisture. This environmental heterogeneity modulated impacts of rainfall and solar radiation. Negative conspecific effects were amplified during rainy years and at dry sites, whereas the positive effects of radiation on survival were more pronounced for seedlings existing at high understory light levels. These results demonstrate that environmental heterogeneity is not only the main driver of seedling survival in this forest but also plays a central role in buffering or exacerbating impacts of climate fluctuations on forest regeneration. Since seedlings represent a key bottleneck in the demographic cycle of trees, efforts to predict the long‐term effects of a changing climate on tropical forests must take into account this environmental heterogeneity and how its effects on regeneration dynamics play out in long‐term stand dynamics. Abstract : Seedlings of Prestoea acuminata var. montana on the forest floor.